LEIGH DISEASE A RARE MITOCHONDRIAL NEUROMETABOLIC DISORDER: Leigh Disease - Afzal, Muhammad; Qureshi, Shaukat Mahmood; ., Lutafullah; Rahim, Asim; Iqbal, Mudassar; Sultan, Mehboob; Ali, Shoaib (Pakistan Armed Forces Medical Journal, 2008)
.